Examining the relationship between CDAI and frailty and its manifestation in Parkinson’s disease: a cross-sectional study - Zeng, Zhaohao; Jin, Wen; Huang, Kunyu; Xiong, Lijiao; Luo, Yu; Li, Guoyang; Zhang, Wenli; Hong, Guo; Mao, Fengju; Xiong, Kaifen; Luo, Xiaoguang (Frontiers in Nutrition, 2024)
Background: Higher intake of antioxidants is associated with reduced risk of various chronic diseases.However, the relationship between composite dietary antioxidants and frailty has not been characterized, especially in neurodegenerative conditions like Parkinson's disease (PD) where frailty is highly prevalent. This study aimed to investigate the association between composite dietary antioxidant index (CDAI), a composite score reflecting antioxidant vitamin and mineral intakes, and frailty risk in the general United States (US) population and PD patients. Methods: Data from 21,354 participants ≥40 years in the National Health and Nutrition Examination Survey (NHANES) 2003-2018 represented the general population sample, while 268 PD patients were analyzed separately. frailty was defined using a validated index. Weighted logistic regression and restricted cubic splines (RCS) examined overall and nonlinear CDAI-frailty associations, adjusting for sociodemographics, lifestyle factors, and comorbidities. Results: In the general population, each unit increase in CDAI was associated with a 3.7% lower likelihood of frailty after full adjustments. Vitamin A, C, E, selenium and carotenoids exhibited Jshaped relationships where frailty risk decreased below intake thresholds of 1093.04 μg, 161.53 mg, 13.66 mg, 109.99 μg, and 5057.50 μg respectively. In contrast, the CDAI-frailty inverse association was weaker among PD patients and only vitamin C (threshold 52.45mg) and zinc (9.35mg) showed nonlinear links.Conclusions: Higher dietary antioxidant intake was associated with lower frailty prevalence in the general US population, with vitamins A, C, E, selenium, and carotenoids exhibiting nonlinear Jshaped relationships. In contrast, these associations were weaker and less consistent among PD patients, with only vitamins C and zinc showing nonlinear correlations. These findings highlight population-specific differences in the role of dietary antioxidants in frailty and suggest the need for personalized nutritional strategies in PD frailty management.